First-Person Effects of Emotional and Informational Messages in Strategic Environmental Communications Campaigns. Issue 6 (2nd November 2017) - Hoewe, Jennifer; Ahern, Lee
ABSTRACT: This study examined the first- and third-person effects of emotional and informational messages, particularly relating to the critical issue areas of energy, the environment, and global warming. Due to intense political polarization on such issues, it also explored the role of political party identification. The results of an experiment indicated that informational messages about the environment produced third-person effects, while environmental advertisements meant to evoke emotion caused first-person effects. Moreover, emotional environmental advertisements appealed more to Republicans and those who did not support a political party. As such, indirect, emotional messages appear to represent an opportunity for strategic environmental communicators to design campaigns that resonate with potentially unreceptive audiences.